TI_GERICHTE 52.2021.168 vom 10. März 2021 , Revoca della licenza di condurre a tempo indeterminato. Riammissione alla guida - TI Tribunale d'appello (2021)
Revoca della licenza di condurre a tempo indeterminato. Riammissione alla guida